Forward and inverse predictive model for the trajectory tracking control of a lower limb exoskeleton for gait rehabilitation: simulation modelling analysis - Muhammad Aizzat, Zakaria; Anwar, P. P. Abdul Majeed; Zahari, Taha; M. M., Alim; Baarath, K. (Institute of Physics Publishing, 2018)
The movement of a lower limb exoskeleton requires a reasonably accurate control method to allow for an effective gait therapy session to transpire. Trajectory tracking is a nontrivial means of passive rehabilitation technique to correct the motion of the patients' impaired limb. This paper proposes an inverse predictive model that is coupled together with the forward kinematics of the exoskeleton to estimate the behaviour of the system. A conventional PID control system is used to converge the required joint angles based on the desired input from the inverse predictive model. It was demonstrated through the present study, that the inverse predictive model is capable of meeting the trajectory demand with acceptable error tolerance. The findings further suggest the ability of the predictive model of the exoskeleton to predict a correct joint angle command to the system.